Implication of Perceived Spaces Toward Visitors' Learning Motivation In Rumah Atsiri Indonesia - Kesumasari, Diana (Universitas Pendidikan Indonesia, 2019)
Rumah Atsiri Indonesia (RAI) is an edu-recreation complex located in Tawangmangu. RAI adopts â€œexperiencing essenceâ€ concept through a comprehensive informal learning about essential oils. RAIâ€™s challenge as an educational leisure setting sets a lead to the main research goal: how visitors perceived spaces in RAI and related them to learning motivation. The observation areas were focused on Museum Gallery and the Essential Oils Collection Gardens. These areas provide most knowledge about essential oils to visitors. Data and information were analyzed qualitatively, by comparing physical settings characteristics of observation areas, person-centered mapping and results of informal interviews and questionnaires. As the result, this research showed that there was relation between physical setting characterictics and visitorsâ€™ learning motivation. Visitors were more motivated to learn in Essential Oils Collection Gardens, especially in outdoor garden. In this area, visitors got richer experiences because visitors had more freedom in exploring essential oil plants. As a performative space that emphasizes visitors as active participants, this area could stimulated visitorsâ€™ emotional and memories through five senses. The adventurous feeling also can be seen from some architectural factors, such as circuitous path with shortcuts, ramps and stairs, which resulting â€œLearning for Funâ€ concept. While in Museum Gallery, visitors circulation and media displays were controlled. As a narrative space that put forward the storyline about the history of essential oils, evidently, visitors got bored easily and show no interest in learning which was reflected in their withdrawal behaviors. Stimulation to visitorâ€™s senses were also limited to sight and hearing, so visitors could not be active participant. Learning motivation was also influenced by intrapersonal factors, but these factors were not analyzed further in this research. Some architectural factors that influenced visitorsâ€™ learning motivation include: space characteristics, binding scale categories, and media display types.Keywords: Essential Oils; Informal Learning; Physical Settings